Making curved composites the pul-aero way. (Research'eu results magazine)
Manufacturing curved polymer composites for aerospace applications has been a labour and resource-intensive practice up till now. The EU-funded PUL-AERO project has now developed a cost-effective, continuous pultrusion process which should finally allow composites to become the material of choice for many aircraft components.